A peirosaurid mandible from the Albian–Cenomanian (Lower Cretaceous) of Algeria and the taxonomic content of Hamadasuchus (Crocodylomorpha, Peirosauridae). (29th March 2023) - Pochat‐Cottilloux, Yohan; Perrier, Vincent; Amiot, Romain; Martin, Jeremy E.
Abstract: Peirosaurids form an extinct clade of terrestrial crocodylomorphs from the Cretaceous of Africa and South America. Here, we describe a new mandibular ramus attributable to Hamadasuchus cf. rebouli from the Albian–Cenomanian of La Gara Samani (Algeria). We propose an emended diagnosis for this taxon, originally described from a left dentary fragment from the Kem Kem Group of Morocco and discuss the assignment of the specimens currently referred to it. Using ontogenetic series of extant crocodylians, we show that several mandibular characters commonly used to differentiate between close taxa instead record intraspecific or ontogenetic variability. In contrast, reliable mandibular characters enable us to propose that the current taxonomic content of Hamadasuchus rebouli should be reduced to three specimens, pending future description of relatable cranial remains. Finally, we demonstrate the importance of mandibular characters in phylogenies, by recovering the new specimen from La Gara Samani as closely related to North African peirosaurids on the basis of a data matrix designed solely on mandibular characters.